2022
DOI: 10.1155/2022/8063382
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ZNF674-AS1 Hinders Proliferation and Invasion of Hepatic Carcinoma Cells through the Glycolysis Pathway

Abstract: Purpose. Long noncoding RNAs (lncRNAs) play important roles in regulating various functions of cells at the levels of transcription and posttranscription. Extensive investigations have illustrated that lncRNAs are critical in the glucose metabolism of tumor cells, but their mechanisms of action need to be further explored. This study evaluates the role of lncRNA ZNF674-AS1 on the apoptosis and proliferation of human hepatic carcinoma cells in vitro through the glucose metabolism and its related mechanisms. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Long noncoding RNA (lncRNA), circular RNA (circRNA) and microRNA targeting PKM2 to affect HCC tumorigenesis and development are one of the current research hotspots. [36,45] noncoding RNA can target PKM2's metabolic enzyme function to affect liver cancer cell metabolic reprogramming, [46][47][48] but also target PKM2's non-metabolic enzyme function to affect HCC tumorigenesis and development. [49,50] Wang C et al [49] found that lncRNA HULC can increase CCND1 expression by miR675-autophagy-PKM2 pathway, further affecting pRB and P21 WAF1/CIP1 expression and increasing liver cancer stem cell proliferation.…”
Section: Noncoding Rna Regulates Pkm2 Non-metabolic Enzyme Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNA (lncRNA), circular RNA (circRNA) and microRNA targeting PKM2 to affect HCC tumorigenesis and development are one of the current research hotspots. [36,45] noncoding RNA can target PKM2's metabolic enzyme function to affect liver cancer cell metabolic reprogramming, [46][47][48] but also target PKM2's non-metabolic enzyme function to affect HCC tumorigenesis and development. [49,50] Wang C et al [49] found that lncRNA HULC can increase CCND1 expression by miR675-autophagy-PKM2 pathway, further affecting pRB and P21 WAF1/CIP1 expression and increasing liver cancer stem cell proliferation.…”
Section: Noncoding Rna Regulates Pkm2 Non-metabolic Enzyme Functionmentioning
confidence: 99%
“…Long noncoding RNA (lncRNA), circular RNA (circRNA) and microRNA targeting PKM2 to affect HCC tumorigenesis and development are one of the current research hotspots. [36,45] noncoding RNA can target PKM2’s metabolic enzyme function to affect liver cancer cell metabolic reprogramming, [46–48] but also target PKM2’s non-metabolic enzyme function to affect HCC tumorigenesis and development. [49,50]…”
Section: The Effect Of Regulating Pkm2 Non-metabolic Enzyme Function ...mentioning
confidence: 99%